2018
DOI: 10.3389/fimmu.2018.00744
|View full text |Cite
|
Sign up to set email alerts
|

CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion

Abstract: Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations but also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 78 publications
6
106
0
Order By: Relevance
“…1). These increases in the older than 60-year age group, compared with younger patients with AD and their respective controls, included markers of cardiovascular risk (myoglobin/MB, GDF15, myeloperoxidase/MPO, ST2), atherosclerosis (CCL4, SORT1), dendritic cells (CD40, CLEC10A 21 regulation (CD274, HMOX1), cell adhesion (CDH3, CDH6), and apoptosis (FAS, TNFRSF21; P < .05) (Figs. 1 and 2B).…”
Section: Systemic Inflammation In the Oldest Patients With Admentioning
confidence: 99%
“…1). These increases in the older than 60-year age group, compared with younger patients with AD and their respective controls, included markers of cardiovascular risk (myoglobin/MB, GDF15, myeloperoxidase/MPO, ST2), atherosclerosis (CCL4, SORT1), dendritic cells (CD40, CLEC10A 21 regulation (CD274, HMOX1), cell adhesion (CDH3, CDH6), and apoptosis (FAS, TNFRSF21; P < .05) (Figs. 1 and 2B).…”
Section: Systemic Inflammation In the Oldest Patients With Admentioning
confidence: 99%
“…MGL is expressed on a range of immune cells including human DCs and macrophages residing in skin and lymph nodes, blood CD1c + DCs, and immature moDCs (van Vliet, Gringhuis, Geijtenbeek, & van Kooyk, , Schutz & Hackstein, , Heger et al, ). To investigate the interaction of MGL with S .…”
Section: Resultsmentioning
confidence: 99%
“…These contrasting outcomes suggest that the context in which MGL is engaged influences how MGL affects DC responses. Indeed, previous reports have indicated that MGL triggering alone does not induce high cytokine secretion by CD1c + DCs but requires costimulation with Toll‐like receptor ligands to differentially affect IL‐8, IL‐10, and TNFα production (Heger et al, ; van Vliet et al, ). Because Toll‐like receptor ligands differ between Gram‐positive and Gram‐negative bacteria, this may explain the different effects on DC cytokine production that we observe here.…”
Section: Discussionmentioning
confidence: 99%
“…For example, each DC cell cluster was found to expresses unique marker genes with established roles in functionally distinct DC subsets (plasmacytoid, maturing CD1c+, CD1c+ and CD8+) ( Fig. 3f-i) 27,28,29,30,31 . It is important to note that all approaches tested failed to sufficiently define all of the discrete CD34+ progenitor cell populations in the entire HCA dataset that were clearly resolved from the independent analysis of these cells, suggesting that these methods are far from perfect.…”
Section: Icgs2 Uniquely Identifies Novel Subpopulations In Ultra Largmentioning
confidence: 99%